Wronskian determinant solutions of the (2 + 1)-dimensional Boiti-Leon-Manna-Pempinelli equation - Najafi, Malihe; Najafi, Mohammad; Arbabi, Somayeh (International Journal of Advanced Mathematical Sciences, 2013)
A set of su?cient conditions consisting of systems of linear partial di?erential equations is obtained which guarantees that the Wronskian determinant solves the (2 + 1)-dimensional Boiti-Leon-Manna-Pempinelli equation in the bilinear form. Our results suggest that more general conditions could be derived by further study.